Effect of strain energy on corrosion behavior of ultrafine grained copper prepared by severe plastic deformation - Rifai M.; Mujamilah M.; Bagherpour E.; Miyamoto H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Effect of strain energy on corrosion behavior of ultrafine-grained (UFG) copper prepared by severe plastic deformation (SPD) was investigated in terms of microstructural evolution. The SPD processed material showed an ultrafine-grained (UFG) structure after grain refinement for several time processes, which will affect mechanical and corrosion behavior Homogeneity can be obtained efficiently through the pressing process commonly known as simple shear extrusion (SSE), which is one of the SPD techniques. Pure copper was processed by SSE for two, four, eight, and twelve passes. The structure of SSE treated sample was observed by laser microscope and transmission electron microscope as well as X-ray diffraction. The corrosion behavior by potentiodynamic polarization curve was observed in modified Livingstone solution, 1 M NaCl, and sulphuric solution. The structure of SSE processed sample showed that the first pass of the SSE processed sample displayed large deformation by developing the elongated grain and sub-grain structure. By increasing the SSE pass number, the grain shape became equiaxed due to excessive strain. The X-ray broadening related to ultrafine-grained (UFG) structure processed SSE on the copper sample, leading to smaller crystallite size, higher microstrain, and higher dislocation density. More homogeneous passive film was developed on the material with UFG structure appearance. However, the current density in 1 M NaCl was decreased by an increment of pass number due to the dissolution of copper metal. The UFG structure has more boundaries than coarse grain structure, and these phenomena show why Cu dissolve ability influences the current density. The grain boundary behaves as the cathodic site.